AI INFLUENCER GOVERNANCE IN DIGITAL PLATFORMS: REGULATORY AND TECHNOLOGICAL PERSPECTIVES IN INDONESIA - Moch. Abdullah Faqih; Intan Putriani; Agradi Aryatama; Rinna Ardina Novriani (NIVEDANA : Jurnal Komunikasi dan Bahasa, 2026)
Advances in artificial intelligence technology have dramatically changed the way we communicate digitally and the marketing strategies we employ. Social media platforms like Instagram, TikTok, and YouTube are now primary venues for interaction and content dissemination. In this context, influencers play a crucial role in shaping audience views and influencing their purchasing choices. Recently, the emergence of AI-based influencers, digital characters created using technologies such as generative artificial intelligence, computer-generated imagery (CGI), and machine learning, has garnered attention. This technology enables the creation of virtual characters that can create content, communicate with users, and engage in promotional activities independently. However, the presence of AI influencers presents several management challenges, particularly those related to transparency, personal data protection, and the impact of algorithms on content dissemination. This study aims to analyze the technological infrastructure supporting the existence of AI influencers and to identify governance challenges within the digital platform realm in Indonesia. The method used is a qualitative approach through normative legal studies and literature analysis. The findings of this study indicate that AI influencers operate within a complex technological ecosystem, interconnecting generative AI systems, digital avatar technology, and platform algorithms. This research also offers a management framework consisting of three layers, namely technology, regulation, and protection for users.